Risk factors for faecal colonisation with Escherichia coli producing extended‐spectrum and plasmid‐mediated AmpC β‐lactamases in dogs. (30th August 2014) - Belas, A.; Salazar, A. S.; Gama, L. T. da; Couto, N.; Pomba, C.
Abstract : The aim of this study was to assess the prevalence and risk factors for faecal carriage of extended‐spectrum β‐lactamase (ESBL) and plasmidic AmpC β‐lactamase (pAmpC) Escherichia coli producers in dogs. A three‐month cross‐sectional study was conducted and 151 rectal swabs were obtained from healthy dogs. ESBL and pAmpC genes were detected by PCR and were sequenced. Logistic regression models were used to investigate risk factors for the carriage of ESBL and pAmpC‐producing E. coli . About 15 per cent of the isolates carried ESBL genes ( bla CTX‐M‐32 n=8, bla CTX‐M‐15 n=5, bla CTX‐M‐1 n=3, bla CTX‐M‐9‐like n=4) and 20 per cent carried pAmpC genes ( bla CMY‐2 n=23, blaCMY‐2‐like n=2). Thirteen dogs carried an E. coli isolate with both an ESBL and a pAmpC gene. One E. coli isolate harboured the human bla DHA‐1 pAmpC gene, which has not been previously reported in companion animals in Europe. Dogs with a history of antimicrobial therapy in the past year had a higher risk of being carriers of ESBL‐producing (P=0.003, OR =7.85) and pAmpC‐producing (P=0.005, OR=6.28) E. coli . Dogs from shelter/breeders were approximately three times more likely to have an ESBL‐ or a pAmpC‐producing E. coli than dogs from private owners. Males have a reduced risk of carrying a pAmpC‐producing E. coli than females (P=0.017, OR =0.28). The knowledge of potential risk factors may help to limit the impact of resistance through implementation of effective control measures and judicious antimicrobial therapy.